Analisis Kemampuan Representasi Matematis Materi SPLDV Ditinjau dari Tipe Kepribadian - Pangestuti, Fadilla Dwi; Prayitno, Sudi; Junaidi, Junaidi; Turmuzi, Muh (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This research was conducted to describe the mathematical representation abilities of eighth-grade students at SMPN 13 Mataram on the topic of Two-Variabel Linear Equation Systems (SPLDV), viewed from the introvert and extrovert personality types. A qualitative research method was used with descriptive approach. The subjects were chosen using purposive sampling and involved 4 students selected based on personality questionnaires and mathematical representation ability tests, followed by interview. Data was collected through non-tes instruments Eysenck Personality Inventory (EPI), essay questions on mathematical representation ability test and interviews which is then analyzed descriptively to find out the differences in verbal, symbolic and visual representation abilities between introvert and extrovert students. The data analysis uses the interactive analysis model from Miles & Huberman. The results showed that introvert students have very good verbal and symbolic representation skills, but still weak in visual representation because none of them could answer correctly. Extrovert students also have good verbal and symbolic representation skills, more confident in answering, but less detailed and tend to rush. Just like introvert, extrovert students also couldn’t represent SPLDV visually in the right way. The main difficulty for both personality types is in converting the information in the problem into a visual representation caused by a lack of experience and practice in drawing graphs.